2006
DOI: 10.1021/jp062443g
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Bias Dependent Photochemical Functionalization of Diamond Surfaces

Abstract: Diamond is an excellent substrate for many sensing and electronic applications because of its outstanding stability in biological and aqueous environments. When the diamond surface is H-terminated, it can be covalently modified with organic alkenes using wet photochemical methods that are surface-mediated and initiated by the ejection of electrons from the diamond. To develop a better understanding of the photochemical reaction mechanism, we examine the effect of applying an electrical bias to the diamond samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 56 publications
5
43
0
Order By: Relevance
“…However, the observed changes are small compared with the size of the avidin molecule. We showed previously that there is no detectable difference in grafting efficiency between NCD and SCD substrates (42). Consequently, we attribute any changes in protein binding between H-terminated and EG6-terminated surfaces to changes in the surface chemistry and not to changes in surface morphology or roughness.…”
Section: Resultsmentioning
confidence: 57%
“…However, the observed changes are small compared with the size of the avidin molecule. We showed previously that there is no detectable difference in grafting efficiency between NCD and SCD substrates (42). Consequently, we attribute any changes in protein binding between H-terminated and EG6-terminated surfaces to changes in the surface chemistry and not to changes in surface morphology or roughness.…”
Section: Resultsmentioning
confidence: 57%
“…15 To fully realize this promise, Hamers and colleagues developed a photochemical approach to graft an alkyl monolayer on a hydrogen-terminated diamond thin film through unsaturated olefin moieties. [16][17][18] On this hybrid material, Yang first fabricated a DNA-modified diamond chip and successfully evaluated its chemical stability by performing a multi-cycle of hybridization-dehybridization with the complementary strand. Intriguingly, the DNA-terminated diamond chip exhibited an excellent signal response and thermal stability for enzymatic reactions, particularly for those under harsh conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][16][17][18] While UV-induced grafting is versatile, it has remained unclear whether there is a single mechanism or whether different combinations of substrates and molecules may react via different reaction pathways. 2,7,16,[19][20][21] The photochemically induced grafting of alkenes to diamond is especially intriguing because the 4.9 eV (254 nm) photon energy typically used is below the 5.5 eV bulk bandgap of diamond and in an optical region where the organic reactant liquids as well as the diamond substrate are nearly transparent (see the Supporting Information). Recently, we showed that UV light can induce photoemission of electrons from diamond into adjacent reactant liquids, 7,21 and studies on diamond and amorphous carbon suggested that this "internal photoemission" process initiates the grafting reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Photochemically induced grafting of alkenes to surfaces has emerged as an effective way to modify the chemical and physical properties of semiconductors. − Recent studies have shown that ultraviolet (UV) light-induced grafting is effective on H-terminated carbon surfaces including metallic (graphitic) forms such as carbon nanofibers , and glassy carbon and semiconducting forms such as amorphous carbon and diamond. − ,− While UV-induced grafting is versatile, it has remained unclear whether there is a single mechanism or whether different combinations of substrates and molecules may react via different reaction pathways. ,,,− The photochemically induced grafting of alkenes to diamond is especially intriguing because the 4.9 eV (254 nm) photon energy typically used is below the 5.5 eV bulk bandgap of diamond and in an optical region where the organic reactant liquids as well as the diamond substrate are nearly transparent (see the Supporting Information). Recently, we showed that UV light can induce photoemission of electrons from diamond into adjacent reactant liquids, , and studies on diamond and amorphous carbon suggested that this “internal photoemission” process initiates the grafting reaction. ,,, However, a number of key questions remain unresolved. While each photoemission event creates a liquid-phase anion and an accompanying hole in the diamond sample, it is unknown what role the anion and hole play in the subsequent grafting reaction .…”
Section: Introductionmentioning
confidence: 99%